Níveis nutricionais de cálcio para aves de corte ISA Label criadas sob semiconfinamento - Pinheiro, S.R.F [UNESP]; Sakomura, N.K [UNESP]; Siqueira, J.C [UNESP]; Marcato, S.M [UNESP]; Dourado, L.R.B [UNESP]; Fernandes, J.B.K [UNESP]; Malheiros, E.B [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2011)
Determinaram-se os níveis nutricionais de cálcio (Ca) para aves, machos e fêmeas, da linhagem ISA Label, nas fases inicial (um a 28 dias), crescimento (28 a 56 dias) e final (56 a 84 dias). Foram realizados três ensaios, um para cada fase, e, em cada ensaio, 480 aves com idade correspondente à fase de criação foram alojadas em 24 unidades experimentais com áreas de abrigo e de pastejo. Foi utilizado delineamento inteiramente ao acaso, em esquema fatorial 4x2 (Ca e sexo), totalizando oito tratamentos com três repetiç ões de 20 aves. Avaliaram-se: ganho de peso (GP); consumo de dieta (CD); conversão alimentar (CA); teores de fósforo (PT), de cálcio (CaT) e de cinzas na tíbia (CT) e resistência à quebra óssea (RQO). Na fase inicial, recomenda-se 1,16% de Ca na dieta, para aves de ambos os sexos, na fase de crescimento, 0,78 e 0,88% de Ca para machos e fêmeas, respectivamente, e, na fase final, 0,69% de Ca na dieta para ambos os sexos.

The nutritional calcium (Ca) levels were determined for ISA Label broilers in the starter (1 to 28 days), growing (28 to 56 days), and finishing (56 to 84 days) phases. Three trials were conducted, one for each phase and in each trial, 480 birds with age corresponding to the phase were housed in 24 experimental units with shelter and pasture areas. The experimental design was completely randomized in a factorial arrangement of 4x2 (Ca levels and sex), totaling eight treatments with three replicates of 20 birds. Body weight gain (BWG); feed intake (FI); feed per gain (FG); contents of phosphorus (TP), calcium (TCa) and ash (TA) in tibia; and bone breaking strength (BSB) were evaluated. At the starter phase, 1.16% of Ca is recommended in the diet for birds of both sexes. At the growing phase, 0.78 and 0.88% of Ca for males and females, respectively, are recommended and at the finishing phase, the level of 0.69% of Ca is recommended in diet for both sexes.
Dietary calcium levels for ISA Label broilers raised in semi-confined system
Keywords: Broilers; Phosphorus; slow-growing birds; nutritional requirement; aves de corte; crescimento lento; Fósforo; requisito nutricional